Computational simulation of concentration by osmotic evaporation of passion fruit juice (Passiflora edullis) (2017)
This study aimed at implementing a comprehensive strategy for the multiphysics simulation of the osmotic evaporation process applied in the concentration of passion fruit juice. The phenomena of mass and momentum transfer were analyzed in Comsol® and Matlab®, using a two-dimensional axial geometry as a simplification of the membrane module. Computer simulations were validated through comparisons with experimental data obtained from osmotic evaporation of passion fruit juice previously ultrafiltrated. The juice was concentrated to 52.25 ± 0.36 (°Brix) of soluble solids, reaching a final flux of 0.63 (kg/m2h) after 6 hours. The concentrate retained the organoleptic and physicochemical quality characteristics of the original juice when it was reconstituted in water. The models and simulations developed can be used to describe, analyze, and efficiently improve the osmotic evaporation process applied to the concentration of juices.